CHANGES IN THE ORAL MUCOSA IN COVID 19 - Turaeva F.A. (Scholar Express Journal, 2021)
Coronavirus can cause a number of inflammatory processes in the oral cavity of patients. In particular, they described the occurrence of ulcers and plaques, as well as cracks on the tongue in an elderly patient hospitalized with COVID-19. In addition, infected people may develop a taste disorder, fungus, candidiasis and other pathological conditions in the mouth. Symptoms can be observed as secondary manifestations of infection, as well as as side effects from taking medications, in particular antibiotics. Moreover, dental problems themselves can serve as a risk factor for infection, since they weaken the protective functions of the body. Therefore, it is advisable to include a dental examination in the list of necessary studies for COVID-19.
Keywords: Oral cavity; taste disorder; fungus; pathological conditions